Współczesna manekinka. O bohaterce Zaplecza Marty Syrwid - Fąfara, Bożena (Tematy i Konteksty, 2015)
Marta Syrwid’s writing enters into subjects which are perceived as taboo. Anorexia, namely striving for unattainable perfection of the body, is such a ‘forbidden’ motif of the novel entitled "Zaplecze". This problem is connected with a lack of acceptance from loved ones which results in both physical and mental emaciation of the novel’s narrator. Syrwid alludes to the motif of a mannequin, in particular a she-mannequin which has been present in literature for centuries. It is fitting to add that the subject of her writing is clearly associated with the model of female writing. Undoubtedly, the value of the interpreted novel arises out of its topicality and tackling of social problems which are usually marginalized.